“Ganzheit” and “Gestalt”. Sketch on theoretical rekonstruction - Herrmann, Theo (Studia Psychologica: Theoria et praxis, 2011)
In this text, the author discusses reconstruction of the terms “Ganzheit“ and “Gestalt”. The author does not intend, however, to describe rather complex historical evolution of the two terms than to use references to historical events for the sole purpose to support clarification of the two terms in focus. It is well-known that terms are always constructed on the base of theoretical requirements. For the reconstruction of “Ganzheit” and “Gestalt”, the author presents theoretical requirements that do not correspond with two “classical” theories, i.e., Wertheimer’s, Köhler’s and Kola’s Berlin Gestalttheory as well as Felix Krueger’s Leipzig theory on structure. The terms “Ganzheit” and “Gestalt” do not refer to real existing phenomena with properties that can be analyzed. They are rather properties of psychic phenomena constructed only in theory. Psychic conditions can be considered as holistic respectively as a wholeness. This is true if single contents of consciousness (Wolfgang Metzger: “Einzelinhalte”) are entities of relational systems. A “Gestalt” (“Gestaltqualität” according to von Ehrenfels) is defined as a “Ganzheit” which is invariant against transformations. - These and other basic assumptions about a “Ganzheit” and “Gestalt” theory will be discussed in detail. At the end of the text, the author draws some conclusions and discusses possible extensions of the theoretical constructs introduced before. In addition, the theoretical concept on “ganzheit” by comparing it with the theories of the Leipzig school is illustrated.